A systems biology approach for diagnostic and vaccine antigen discovery in tropical infectious diseases. Issue 5 (October 2015) - Liang, Li; Felgner, Philip L.
<x xml:space="preserve">Abstract</x> Purpose of review There is a need for improved diagnosis and for more rapidly assessing the presence, prevalence, and spread of newly emerging or reemerging infectious diseases. An approach to the pathogen-detection strategy is based on analyzing host immune response to the infection. This review focuses on a protein microarray approach for this purpose. Recent findings Here we take a protein microarray approach to profile the humoral immune response to numerous infectious agents, and to identify the complete antibody repertoire associated with each disease. The results of these studies lead to the identification of diagnostic markers and potential subunit vaccine candidates. These results from over 30 different organisms can also provide information about common trends in the humoral immune response. Summary This review describes the implications of the findings for clinical practice or research. A systems biology approach to identify the antibody repertoire associated with infectious diseases challenge using protein microarray has become a powerful method in identifying diagnostic markers and potential subunit vaccine candidates, and moreover, in providing information on proteomic feature (functional and physically properties) of seroreactive and serodiagnostic antigens. Combining the detection of the pathogen with a comprehensive assessment of the host immune response will provide a new understanding of the correlations between specific causative agents, the host response, and the clinical manifestations of the disease.